2017
DOI: 10.1371/journal.pone.0187150
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq transcriptome analysis of formalin fixed, paraffin-embedded canine meningioma

Abstract: Meningiomas are the most commonly reported primary intracranial tumor in dogs and humans and between the two species there are similarities in histology and biologic behavior. Due to these similarities, dogs have been proposed as models for meningioma pathobiology. However, little is known about specific pathways and individual genes that are involved in the development and progression of canine meningioma. In addition, studies are lacking that utilize RNAseq to characterize gene expression in clinical cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 71 publications
(69 reference statements)
1
18
0
Order By: Relevance
“…Human-telomerase reverse transcriptase expression has been described in a number of canine meningioma subtypes; however, has not been evaluated in a prognostic setting (138). Somatostatin receptor-2 expression has recently been described in a variety of canine meningioma subtypes, a finding that is supported by RNAseq data analysis of canine meningioma that revealed increased expression of somatostatin receptors (126, 139). The significance of this finding is unclear; however, similar findings have been noted in a number of human tumors, including meningioma.…”
Section: Meningiomamentioning
confidence: 66%
See 1 more Smart Citation
“…Human-telomerase reverse transcriptase expression has been described in a number of canine meningioma subtypes; however, has not been evaluated in a prognostic setting (138). Somatostatin receptor-2 expression has recently been described in a variety of canine meningioma subtypes, a finding that is supported by RNAseq data analysis of canine meningioma that revealed increased expression of somatostatin receptors (126, 139). The significance of this finding is unclear; however, similar findings have been noted in a number of human tumors, including meningioma.…”
Section: Meningiomamentioning
confidence: 66%
“…Canine meningiomas are widely infiltrated by inflammatory cells including an abundance of neutrophils, either associated with or unassociated with areas of necrosis, large numbers of macrophages and an abundance of lymphocyte subtypes (124). Initial immunohistochemical analysis for interleukin 6 and 8 expression failed to yield significant expression levels; however, RNA transcriptome analysis of canine meningioma revealed overexpression in a number of immunomodulatory genes (125, 126). Chondroid and osseous metaplasia are sporadically seen in various subtypes, although they are most commonly seen in the optic nerve-associated meningiomas.…”
Section: Meningiomamentioning
confidence: 99%
“…Moreover, survival analysis (Survival package with logrank test; threshold value of P value < 0.05) of key genes related to resting mast cells showed that the risk model constructed based on 9 key genes (CXCL8, MYC, CXCL2, CXCL3, TNFAIP3, FOSL1, HIST1H2BN, BCL2A1 and SLC2A3) could predict the prognosis of patients with meningioma. A previous study reported that MYC expression is dysregulated in human meningioma, indicating its potential role in oncogenic processes [37]. Cai et al [38] found that c-MYC in meningioma is targeted by RIZ1 to negatively regulate the ubiquitin-binding enzyme E2C/UbcH1.…”
Section: Discussionmentioning
confidence: 99%
“…AQP1 gene expression was up-regulated in endometriosis (Figure 1(b)). AQP1 was then predicted to interact with topoisomerase 2-beta (TOP2B) by PPI (Figure 1 (c)), which was correlated to the Wnt/β-catenin signaling pathway [12,26,27]. All in all, AQP1 gene is highly expressed in endometriosis and is related to Wnt signaling pathway in silico.…”
Section: Aqp1 Gene Expression Is Upregulated In Endometriosismentioning
confidence: 99%